2022
DOI: 10.1002/dc.24958
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphologic features of thyroid nodules harboring thyroid adenoma‐associated fusion: A single institutional review of 11 cases

Abstract: Background Thyroid adenoma‐associated (THADA) fusions are being identified more frequently with increased preoperative molecular testing on indeterminate thyroid fine‐needle aspirates (FNA). However, data on cytomorphologic features of THADA‐fusion thyroid lesions are limited. We examined cytomorphologic features of a THADA‐fusion thyroid FNA cohort with clinical, radiologic, and histologic data. Methods Our THADA fusion FNA cohort included 11 specimens from 11 patients with a mean age and F:M ratio of 56.5 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Accordingly, it is feasible that the cytologic features described in our cohort are not representative of the entire cytomorphologic spectrum of DICER1‐altered thyroid lesions. We also recognize that the relatively bland cytomorphologic features seen with DICER1‐altered thyroid FNAs overlap with features reported for FNAs from other RAS‐like thyroid lesions 15,16 . Thus, it would be difficult to conclude preoperatively the presence of a DICER1 alteration primarily on cytomorphology.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Accordingly, it is feasible that the cytologic features described in our cohort are not representative of the entire cytomorphologic spectrum of DICER1‐altered thyroid lesions. We also recognize that the relatively bland cytomorphologic features seen with DICER1‐altered thyroid FNAs overlap with features reported for FNAs from other RAS‐like thyroid lesions 15,16 . Thus, it would be difficult to conclude preoperatively the presence of a DICER1 alteration primarily on cytomorphology.…”
Section: Discussionmentioning
confidence: 74%
“…We also recognize that the relatively bland cytomorphologic features seen with DICER1-altered thyroid FNAs overlap with features reported for FNAs from other RAS-like thyroid lesions. 15,16 Thus, it would be difficult to conclude preoperatively the presence of a DICER1 alteration primarily on cytomorphology. seen in all but one of our resected cases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many experts advise stringent adherence to the major diagnostic features of PTC to avoid false-positive diagnosis [20]. Interestingly, some authors have also found important genotype-phenotype correlates, with an overrepresentation of THADA gene fusions in benign thyroid lesions with occasional nuclear grooves [21]. It is also equally important to note that other malignant tumors of the thyroid gland can display few but not all cytological features of PTC, such as intranuclear grooves or occasional nuclear inclusions, features that may be encountered in medullary thyroid carcinoma (MTC) and oncocytic thyroid carcinoma [22,23].…”
Section: Teasing Out "Atypia" In Thyroid Glandmentioning
confidence: 99%
“…[11][12][13] Interestingly, despite the association between IGF2BP3 and cancer and though some thyroid neoplasms with THADA-IGF2BP3 fusions can be large sized, overall thyroid lesions with such fusions appear to be low-risk neoplasms such as non-invasive follicular thyroid neoplasms with papillary-like nuclear features (NIFTP). [14][15][16] However, only a few case series are available within the literature [15][16][17][18][19][20] and at least one study supports evidence that IGF2BP3 is an adverse prognostic factor for a subset of poorly-differentiated thyroid carcinomas. 21 Here, we sought to investigate all instances of thyroid nodules with THADA-IGF2BP3 fusions at our institution to define the significance of this molecular alteration more clearly in FNA specimens.…”
mentioning
confidence: 99%